The Encyclopedia of 20Th Century Conflict : Air Warfare - Cooksley, Peter G. (London Arms and Armour Press, 1997)
Opslagsbog vedr. luftkrigshistorien i det 20.århundrede
Include Illustration
Keywords: Air warfare -- Airplanes, Military